A high-throughput RNA-Seq approach to elucidate the transcriptional response of Piriformospora indica to high salt stress - Nivedita (Nature Portfolio, 2021)
Abstract Piriformospora indica, a root endophytic fungus, augments plant nutrition and productivity as well as protects plants against pathogens and abiotic stresses. High salinity is a major problem faced by plants as well as by microbes. Until now, the precise mechanism of salt stress tolerance in P. indica has remained elusive. In this study, the transcriptomes of control and salt-treated (0.5 M NaCl) P. indica were sequenced via the RNA-seq approach. A total of 30,567 transcripts and 15,410 unigenes for P. indica were obtained from 7.3 Gb clean reads. Overall 661 differentially expressed genes (DEGs) between control and treated samples were retrieved. Gene ontology (GO) and EuKaryotic Orthologous Groups (KOG) enrichments revealed that DEGs were specifically involved in metabolic and molecular processes, such as “response to salt stress”, “oxidoreductase activity”, “ADP binding”, “translation, ribosomal structure and biogenesis”, “cytoskeleton”, and others. The unigenes involved in “cell wall integrity”, “sterol biosynthesis”, and “oxidative stress” such as Rho-type GTPase, hydroxymethylglutaryl-CoA synthase, and thioredoxin peroxidase were up-regulated in P. indica subjected to salt stress. The salt-responsive DEGs have shown that they might have a potential role in salt stress regulation. Our study on the salt-responsive DEGs established a foundation for the elucidation of molecular mechanisms related to P. indica stress adaptation and a future reference for comparative functional genomics studies of biotechnologically important fungal species.